Changing life expectancy in the 1980s: why was Denmark different from Sweden?. Issue 4 (August 1996) - Chenet, L; Osler, M; McKee, M; Krasnik, A
Abstract : OBJECTIVE: To identify the contribution from specific causes of death to the changes in life expectancy at birth in Denmark relative to Sweden in different age groups during the 1980s and to compare the difference in life expectancy between the two countries in 1990. DESIGN: Mortality data from WHO mortality tapes grouped in smaller series of clinically meaningful categories were used to calculate the contribution of each of these categories at each 10 year age group to the difference in life expectancy at birth in each country between 1979 and 1990 and between the two countries. SETTING: Denmark and Sweden. RESULTS: Between 1979 and 1990 life expectancy increased in both Denmark and Sweden. However, the increase in Sweden was more than two years while that in Denmark was less than one year. In both countries a decrease in cardiovascular disease mortality contributed most to the increase in life expectancy in males as well as females. In both sexes the smaller increase in life expectancy in Denmark was a result of differences in mortality trends in cardiovascular diseases and respiratory and non-respiratory cancers. CONCLUSION: Over a short time two Nordic countries experienced remarkable but different changes in mortality. These findings suggest that mortality rates are sensitive to even minor differences in social and cultural factors across countries and over short time periods.